Fatiha book: meanings, and jurisprudence provisions (Journal of Human Sciences, 2018)
Observers find the commentators in Surat Al-Fatihah: that most of them go on in his words about their meanings and names, and some of them devised symbols for everything that came in the Koran of the detective, which is with few verses and summarized the whale of the meanings of the Koran, and its main purposes in general, dealt with the origins of religion and its branches, and discussions of faith and worship Legislation, and the individual God - the Almighty - to worship, and the use of it in the whole matter, and guidance to the right path, and that enough slaves evil way of the angered and misguided, and therefore imposed God Almighty repeated in every prayer.  Since the chapeau of the book is recited in every rak'ah of prayer, the invocation of its meanings and management in the mind of the worshiper is required, and we need to manage their meanings from a systematic perspective, and seek the wonders of the ability of God and the wisdom of the wisdom to stand on its verses, to be closer to the beholder and explained when meditation, because Prayer is a link between the servant and his Lord, and the worshiper after he opens his prayer in takbeerihraam, he calls upon his Lord to read this surah .Hence, we have seen the importance of preparing an analytical study in the field of interpretation of the Holy Quran, by identifying the meanings of Surat Al-Fatiha by following them in the books of interpretation . After the initial induction in the meanings of this Sura, it turned out the magnitude of the size of the subject, and the greatness of the Sura on the lack of words and brief, and he was motivated to stand on its meanings, and study its jurisprudence.